The AMPK activator metformin improves recovery from demyelination by shifting oligodendrocyte bioenergetics and accelerating OPC differentiation - Narine, Mohanlall; Azmi, Maryam A.; Umali, Martin; Volz, Ashley; Colognato, Holly (Frontiers in Cellular Neuroscience, 2023)
Multiple Sclerosis (MS) is a chronic disease characterized by immune-mediated destruction of myelinating oligodendroglia in the central nervous system. Loss of myelin leads to neurological dysfunction and, if myelin repair fails, neurodegeneration of the denuded axons. Virtually all treatments for MS act by suppressing immune function, but do not alter myelin repair outcomes or long-term disability. Excitingly, the diabetes drug metformin, a potent activator of the cellular "energy sensor" AMPK complex, has recently been reported to enhance recovery from demyelination. In aged mice, metformin can restore responsiveness of oligodendrocyte progenitor cells (OPCs) to prodifferentiation cues, enhancing their ability to differentiate and thus repair myelin. However, metformin's influence on young oligodendroglia remains poorly understood. Here we investigated metformin's effect on the temporal dynamics of differentiation and metabolism in young, healthy oligodendroglia and in oligodendroglia following myelin damage in young adult mice. Our findings reveal that metformin accelerates early stages of myelin repair following cuprizone-induced myelin damage. Metformin treatment of both isolated OPCs and oligodendrocytes altered cellular bioenergetics, but in distinct ways, suppressing oxidative phosphorylation and enhancing glycolysis in OPCs, but enhancing oxidative phosphorylation and glycolysis in both immature and mature oligodendrocytes. In addition, metformin accelerated the differentiation of OPCs to oligodendrocytes in an AMPK-dependent manner that was also dependent on metformin's ability to modulate cell metabolism. In summary, metformin dramatically alters metabolism and accelerates oligodendroglial differentiation both in health and following myelin damage. This finding broadens our knowledge of metformin's potential to promote myelin repair in MS and in other diseases with myelin loss or altered myelination dynamics.